Patterns of motor control in trained cyclists are highly consistent between athletes yet unique to the muscle of interest - Chapman, A.; Vicenzino, B.; Blanch, P.; Hodges, P. (Australian Conference of Science and Medicine in Sport and Third National Sports Injury Prevention Conference: 2003. Tackling the barriers of performance and participation, 2003)
During cycling, muscles of the distal lower limb are thought to provide a significant contribution to net propulsive output and to assist in maintaining the control of foot, ankle and knee joints. However, there are currently limited in-vivo data to support theories of motor control for these muscles during cycling. Existing studies are contradictory and are characterized by inadequate methodology. In this study, patterns of motor control for the tibialis anterior (TA), tibialis posterior (TP), peroneus longus (PL), gastrocnemius lateralis (GL) and soleus (SOL) were investigated in trained cyclists using selective intramuscular electrodes. For all muscles, patterns of recruitment were highly consistent between athletes. The TP, PL and SOL displayed a monophasic pattern of recruitment and were primarily active during the downstroke. TA and GL were recruited in a biphasic manner. TP displayed a more tonic pattern of activation than other muscles. Despite the contrasting anatomical functions of TA and GL, a coactivation strategy was evident between these muscles during both phases of the pedal stroke. Contrary to existing hypotheses, data indicate that little coactivation exists between TP and PL. For each individual athlete, recruitment patterns of TP and SOL were more consistent than those of TA, PL and GL. This study provides evidence that trained cyclists adopt homogeneous patterns of motor control, and that these athletes utilize a range of motor control strategies in the distal lower limb. These data provide a basis for further investigation of neuromuscular dysfunction in cyclists, and the development of cycling-specific motor control strategies.